A COMPARATIVE ANATOMICAL STUDY OF THE LOWER EPIDERMIS OF LEAVES OF THE GENUS AEGILOPS - Hijran Mohammed Obaid Al- Dulaimi, Ruqayah Manoon Hasan Alnomani (Chelonian Research Foundation, 2024)
In this paper leaf structure of Six Iraqi species of Aegilops L. have been anatomically examined. It was observed that the anatomical characters have high variation in the length of long cells in both stomatal and non- stomatal rows, length and number of stomata in microscopic field, the number of short cells, indumentum properties such as type of prickle hairs and macro- hairs, the blade and keel outline, the shape of abaxial and adaxial sclerenchyma, and bulliform cells arrangement, Finally the study show that anatomical characteristics of the leaf blade vary between studied taxa. Key words: Anatomy, Aegilops , Poaceae, Variation